Migrations and Population Turnover in Spain: The Territorial Gap, 2002-2021 - Damoun, Osama (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2025)
Global migrations constitute the main factor of demographic change in post-transitional societies, such as Spain, which has experienced two waves of international migration over the past two decades shaped by the economic cycle. This study analyses these changes at the provincial level and their impact on territorial imbalances, evaluating population renewal and the relative contributions of natural growth and migration. The results highlight the growing role of migrations, particularly international ones, in population turnover. Two distinct patterns emerge: a temporal pattern, marked by an initial phase of record-high inflows and widespread population growth, followed by a deceleration and a second wave characterized by lower migration volumes but a more pronounced demographic impact; and a geographical pattern, defined by three demographic systems: regions dominated by international migration, areas experiencing significant native emigration, and others where aging and mortality are the prevailing demographic dynamics.
Keywords: population turnover; migration cycles; natural growth; fast demography; international immigration